Thirukural and Vethathiriyam: A comparative study - Manonmany P Parthiban (Yoga-Mimamsa, 2019)
Thirvalluvar was a Tamil Philosopher belonging to the pre Christian Era. The government has given his birth date as late as 31 BC. Some scholars date Thiruvalluvar and his work “Thirukural ”as early as 500 BC. Vethathiri Maharishi is a Yogi and Spiritual leader of the 21st century. He was a Siddha, Ayurvedic, Homeopathic practitioner and Founder of the World Community Service Center. This study tries to compare the message of the 2500 year old Thirukural with the teaching of the modern day yogi Vethathiri Maharishi. Maharishi always stressed on the “Art of Living ”as a way to balance and achieve inner as well as world peace. He took this term from the message of Thirukural and in this study we will compare how successfully Maharishi has preached the essence of Thirukural to the modern world.